Measurement invariance of the GAD-5 Generalized Anxiety Disorder Scale in a Mexican general population sample - Astudillo-García, Claudia I.; Austria-Corrales, Fernando; Rivera-Rivera, Leonor; Reynales-Shigematsu, Luz Myriam; Gómez-García, José Alberto; Séris-Martinez, Marina; Jiménez-Tapia, Alberto; Robles, Rebeca; Morales-Chainé, Silvia; López-Montoya, Alejandra; Cuevas-Renaud, Corina; Toledano-Toledano, Filiberto (Frontiers in Psychiatry, 2022)
The primary objective of this study was to evaluate the measurement of invariance by sex, age, and educational level of an online version of the Generalized Anxiety Disorder Scale in a five-item version (GAD-5). Configural, metric, scalar, and strict invariance were evaluated using data from 79,473 respondents who answered a mental health questionnaire during the COVID-19 pandemic in Mexico. The sex variable was classified as male or female; age was categorized as minors, youth, young adults, adults, and older adults; and educational level was divided into basic, upper secondary, higher, and graduate education. To test for configural invariance, confirmatory factor models were constructed. For metric invariance, equality restrictions were established for the factor loadings between the construct and its items; for scalar invariance, equality restrictions were established between the intercepts; strict variance implied the additional restriction of the residuals. Statistical analysis was performed in R software with the lavaan package (Rosseel, 2012). The results show that with respect to sex, age, and educational level, configural and metric measurement invariance was confirmed (∆CFI < 0.002; ∆RMSEA < 0.015). However, with respect to scalar and strict invariance, the results showed significant differences regarding the fit model (∆CFI > 0.002; ∆RMSEA > 0.015). We conclude that the GAD-5 presents configural and metric invariance for sex, age, and educational level, and scalar invariance for sex and age groups. However, the scale does not demonstrate strict invariance. We discuss the implications and suggest that this result could be related to the evaluation of sociodemographic variables.